A modelling exercise on the importance of ternary alkaline earth carbonate species of uranium(VI) in the inorganic speciation of natural waters. (April 2015) - Vercouter, Thomas; Reiller, Pascal E.; Ansoborlo, Eric; Février, Laureline; Gilbin, Rodolphe; Lomenech, Claire; Philippini, Violaine
Highlights: The U(VI) speciation in natural waters has been modelled through a modelling exercise. The results evidence the importance of alkaline earth U(VI) carbonate complexes. Possible solubility-controlling phases were reported and discussed. The differences were related to the choice and reliability of thermodynamic data. Databases need to be improved for reliable U(VI) speciation calculations. Abstract: Predictive modelling of uranium speciation in natural waters can be achieved using equilibrium thermodynamic data and adequate speciation software. The reliability of such calculations is highly dependent on the equilibrium reactions that are considered as entry data, and the values chosen for the equilibrium constants. The working group "Speciation" of the CETAMA (Analytical methods establishment committee of the French Atomic Energy commission, CEA) has organized a modelling exercise, including four participants, in order to compare modellers' selections of data and test thermodynamic data bases regarding the calculation of U(VI) inorganic speciation. Six different compositions of model waters were chosen so that to check the importance of ternary alkaline earth carbonate species of U(VI) on the aqueous speciation, and the possible uranium solid phases as solubility-limiting phases. The comparison of the results from the participants suggests (i) that it would be highly valuable for end-users to review thermodynamic constants of ternary carbonate species of U(VI) in a consistent way and implement them in available speciation data bases, and (ii) stresses the necessary care when using data bases to avoid biases and possible erroneous calculations.